Research Methods - AR354 - 202301 - Wong Lent, Luisa Cristina (2023)
Description of Course This course is about answering questions and solving problems in urban environments and introducing students to creative problem-solving strategies in the urban context. Students will get to choose their topic of interest to study during the term, e.g., transportation, the environment, social equity, etc. Ideally, their topic can inform the development of a senior capstone in subsequent semesters. This course will train students to quantitatively and qualitatively analyze real world data used in the planning and design of the built environment. Students will gain first-hand experience in the research process: forming research questions and figuring out how to best answer those research questions. Students will develop key skills including identifying and analyzing data sources, building datasets, learning descriptive statistics, analyzing trends, and visualizing data. The course will culminate in students developing a proposal that they can use for their Senior Capstone. Course Prerequisites or Co-requisites Students intending to enroll in this course must have successfully completed their second semester of English. Course Name: SBE 480/580 - Research Methods 3 Credit Hours Instructors: Dr. Nataliya Apanovich (Arizona) MSc Cristina Wong (Peru) Course Final: July 6th 1-4pm (Peru time)